Voyage au centre de la chair : l’exploration miniature du corps humain dans les jeux vidéo - Fleur Hopkins (ReS Futurae)
This paper studies the theme of traveling through a body, human or even monstrous, in science fiction video games. We can identify five types of inner travels : a struggle with a living being, who has just swallowed the hero to destroy him and that needs to be annihilated from the inside ; a marvelous exploration meant to learn more about the human body ; shooting or strategy games that take place within the body ; an army patrol in a sick body, in order to fight the disease that is taking over the player ; augmented and virtual reality displays that enable doctors to see through the body, made transparent. The idea of miniaturization using a shrinking ray or a fairy is widespread. However, a large number of technology innovations appear as early as the nineteenth century and associates change of scale with discovering inner space. The screen display and the game controls, reminding us of the surgeon’s operational theatre, stage the milieu intérieur in an organic and virtual environment. Video games become an exploratory space to develop the imagination of the journey to the center of the flesh.